PENGARUH KERJASAMA TIM, LINGKUNGAN KERJA, DAN BEBAN KERJA TERHADAP KINERJA BERDASARKAN PERSEPSI KARYAWAN PT.RECON SARANA UTAMA BALIKPAPAN - Nainggolan , Hermin (UNIKA Santo Thomas, 2023)
This study aims to determine the effect of teamwork, work environment and workload on performance based on the perceptions of employees of PT. Recon Sarana Utama Balikpapan partially and simultaneously. The research data was obtained from reports on employee performance results for 3 years, namely the 2019-2021 period with a total population and sample of 65 employees. By using a multiple linear regression test. Based on the results of the partial hypothesis research test showing that the independent variable (teamwork) has a positive and significant effect on (performance) the tcount is 15.481 > ttable 1.670 and a significance of 0.000 <0.05. The independent variable (work environment) partially has no positive and insignificant effect on (performance) obtained a tcount of 0.383 < ttable of 1.670 and a significance value of 0.703 > 0.05. The independent variable (workload) partially has no positive and insignificant effect on (performance) obtained a tcount of 0.420 < ttable of 1.670 and a significance value of 0.676 > 0.05. Simultaneously showing that the variable teamwork, work environment and workload have a significant effect on performance obtained fcount 80.078 > ftable 2.523 and a significance value of 0.000 <0.05.